A Modeling Investigation on High-Speed Broad Spectrum Filtering System Based on Electric Fluid Technology - Jun Wu; Qiuyue Zhu; Zhiyang Qi; Jun Xia; Chenliang Chang; Qilong Wang; Baoping Wang (IEEE Photonics Journal, 2017)
By combining advanced fluid control technology with surface plasmonic resonance phenomenon, we could take advantage of various unique characteristics of plasmonics without changing the original structure to realize a tunable color filtering system. By modifying the wetting properties of solid surface with an electric field, electro-fluid control technology could tune the curvature of two-phase fluid interface continuously and, therefore, change the distributions of silver nanoparticles on the interface accordingly. Based on this fluidic optical design, we investigated the influencing factors of color filtering performance by modeling, finally got an optimized design to achieve broad spectrum filtering system. As the color filtering function is realized simply and rapidly by charging, and therefore, this design could improve the efficiency of the electro-optical systems and is a promising idea for many applications, such as the dynamic display devices.